2022
DOI: 10.1101/2022.04.11.487905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous viral elements reveal associations between a non-retroviral RNA virus and symbiotic dinoflagellate genomes

Abstract: Endogenous viral elements (EVEs) offer insight into the evolutionary histories and hosts of contemporary viruses. This study leveraged DNA metagenomics and genomics to detect and infer the host of a non-retroviral dinoflagellate-infecting +ssRNA virus (dinoRNAV) common in coral reefs. As part of the Tara Pacific Expedition, this study surveyed 269 newly sequenced cnidarians and their resident symbiotic dinoflagellates (Symbiodiniaceae), associated metabarcodes, and publicly available metagenomes, revealing 178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Dinoflagellate‐infecting RNA viruses (dinoRNAVs) are positive‐sense, single‐stranded RNA viruses hypothesized to infect the dinoflagellate symbionts (Family Symbiodiniaceae) that live in the tissues of reef‐building stony corals (Correa et al., 2013; Grupstra et al., 2022; Veglia et al., 2022). Although dinoRNAVs can be prevalent in coral colonies (Grupstra et al., 2022; Howe‐Kerr et al., 2023; Montalvo‐Proaño et al., 2017; Veglia et al., 2022), it is unclear how dinoRNAVs (or Symbiodiniaceae infected by dinoRNAVs) are transmitted among colonies. Recent work has shown that corallivorous (coral‐eating) fishes disperse 100 s of millions of live Symbiodiniaceae cells across reefscapes in their faeces each day (Grupstra et al., 2021).…”
Section: Applying Vampirus To Study a Novel Environmental Rna Virus D...mentioning
confidence: 99%
“…Dinoflagellate‐infecting RNA viruses (dinoRNAVs) are positive‐sense, single‐stranded RNA viruses hypothesized to infect the dinoflagellate symbionts (Family Symbiodiniaceae) that live in the tissues of reef‐building stony corals (Correa et al., 2013; Grupstra et al., 2022; Veglia et al., 2022). Although dinoRNAVs can be prevalent in coral colonies (Grupstra et al., 2022; Howe‐Kerr et al., 2023; Montalvo‐Proaño et al., 2017; Veglia et al., 2022), it is unclear how dinoRNAVs (or Symbiodiniaceae infected by dinoRNAVs) are transmitted among colonies. Recent work has shown that corallivorous (coral‐eating) fishes disperse 100 s of millions of live Symbiodiniaceae cells across reefscapes in their faeces each day (Grupstra et al., 2021).…”
Section: Applying Vampirus To Study a Novel Environmental Rna Virus D...mentioning
confidence: 99%
“…Dinoflagellate-infecting RNA viruses (dinoRNAVs) are positive-sense, single-stranded RNA viruses hypothesized to infect the dinoflagellate symbionts (Family Symbiodiniaceae) that live in the tissues of reef-building stony corals (Correa et al, 2013;Veglia et al, 2022). Although dinoRNAVs can be prevalent in coral colonies Howe-Kerr et al, 2022;Montalvo-Proaño et al, 2017;Veglia et al, 2022), it is unclear how dinoRNAVs (or Symbiodiniaceae infected by dinoRNAVs) are transmitted among colonies. Recent work has shown that corallivorous (coral-eating) fishes disperse 100s of millions of live Symbiodiniaceae cells across reefscapes in their feces each day (Grupstra et al, 2021).…”
Section: Rna Virus Study Descriptionmentioning
confidence: 99%
“…Overall, it was challenging to determine whether the identified transcripts stemmed from genomes of independent viruses or from integrated virus sequences within the host's genome since the study was based solely on RNA-Seq data. It is well-known that endogenous viral elements (EVEs) of DNA and non-retroviral RNA viruses are widespread across invertebrate genomes and these EVEs can be transcriptionally active (ter Horst et al, 2019;Veglia et al, 2023). Furthermore, EVEs of invertebrate genomes originate from a wider range of viral families when compared to vertebrate genomes and the abundance and diversity of EVEs is highly variable even between closely related invertebrate species (Gilbert & Belliardo, 2022).…”
Section: Read Taxonomic Classification Into Viral Familiesmentioning
confidence: 99%